Strength Characteristics of Geopolymer Concrete Made with Fly Ash and Calcium Carbide Residue: A Sustainable Alternative to Traditional Concrete - Peddireddy Sreekanth Reddy; Ambreshwar; Satish K; Anu Jaiswal; Rahul Jaiswal; Rohit Kumar Yadav (Innovative Solutions: A Systematic Approach Towards Sustainable Future, Edition 1, 2025)
Rapid urbanization and infrastructure development, leads to the depletion of natural resources. In addition, the industrial expansions to meet the demand of materials leading to the generation of waste by products in multiple means. Both the activities contributing to the global warming and leaving carbon footprints on the environment. To address these issues, the current study intends to employ these wastes by products i.e. Fly ash (FA) and Calcium Carbide Residue (CCR) in the production of geopolymer concrete as an alternative to traditional concrete. Cement is replaced with FA of 15% and CCR of 0%, 10%, 20%, 30%, 40%, 50% and RCA of 25%. Employing these proportions, the prepared geopolymer concrete is investigated for workability and strength characteristics. These properties of GPC were by determined by subjecting the concrete to slump cone and compressive strength test. From the test results, it is observed that the workability declined with increment in CCR content. The strength characteristics of the specimen increased to 136 Mpa from 75 Mpa. The GPC prepared in the current can be a cost effective and declines the environmental issues.